Association Between Matrix Metalloproteinase-3 Activity and Glomerular Filtration Rate and Albuminuria Status in Patients With Type 2 Diabetes Mellitus (Iranian Journal of Kidney Diseases, 2018)
Introduction. Diabetic nephropathy is pictured as matrix accumulation and thickening of glomerular basal membrane. Matrix metalloproteinases (MMPs) are major proteases involved in extracellular matrix degradation. Moreover, plasminogen activator inhibitor-1 (PAI-1) primarily regulates plasmin dependent proteolysis. It plays a role in renal fibrosis causing extracellular matrix accumulation through inhibition of plasmin-dependent extracellular matrix degradation. This study investigated PAI-1 serum level and MMP-3 activity and their correlation with glomerular filtration rate in patients with diabetes mellitus. Materials and Methods. In a case-control design, serum PAI-1 concentrations and MMP-3 activity were measured in 80 patients with normoalbuminuria, microalbuminuria, and macroalbuminuria. Receiver operating characteristics curve analysis was used to assess the diagnostic accuracy of MMP-3 activity in discriminating albuminuria. Results. In the patients with microalbuminuria, serum PAI-1 levels were higher compared with macroalbuminuric patients (P < .001). The patients with macroalbuminuria exhibited a significantly lower MMP-3 activity than the patients with microalbuminuria and normoalbuminuria (P < .001). No significant correlation was found between serum MMP-3 activity and serum PAI-1 levels in those with normoalbuminuria, microalbuminuria, and macroalbuminuria. The MMP-3 activity had a strong positive correlation with estimated glomerular filtration (r = 0.853, P < .001). Conclusions. We found that there was a positive correlation between glomerular filtration rate and MMP-3 activity in diabetic patients. This concludes that MMP-3 may have a role in the pathogenesis of diabetic nephropathy progressions towards macroalbuminuria, and therefore, MMP-3 activity may be used in evaluating albuminuria status.